Exogenous Testosterone Enhances the Reactivity to Social Provocation in Males - Wagels, Lisa; Votinov, Mikhail; Kellermann, Thilo; Eisert, Albrecht; Beyer, Cordian; Habel, Ute (Frontiers in Behavioral Neuroscience, 2018)
Testosterone affects human social behavior in various ways. While testosterone effects are generally associated with muscular strength and aggressiveness, human studies also point towards enhanced status–seeking motives after testosterone administration. The current study tested the causal influence of exogenous testosterone on male behavior during a competitive provocation paradigm. In this double blind, randomized, placebo-controlled study, 103 males were assigned to a placebo or testosterone group receiving a colorless placebo or testosterone gel. To induce provocation, males played a rigged reaction time game against an ostensible opponent. When participants lost, the opponent subtracted money from the participant who in return could subtract money from the ostensible opponent. Participants subjectively indicated anger and self-estimated treatment affiliation (testosterone or placebo administration). A trial-by-trial analysis demonstrated that provocation and success during the repeated games had a stronger influence on participants’ choice to reduce money from the opponent if they had received testosterone. Participants who believed to be in the testosterone group were angrier after the experiment and increased monetary reductions during the task course. In line with theories about mechanisms of testosterone in humans, provocation is shown to be necessary for the agency of exogenous testosterone. Thus, testosterone reinforces the conditional adjustment of aggressive behavior but not aggressive behavior per se. In contrast undirected frustration is not increased by testosterone but probably interferes with cognitive appraisals about biological mechanisms of testosterone.